Finite Element Analysis of Soccer Heading - Mohd Hasnun Ariff, Hassan; Zahari, Taha (Elsevier Ltd, 2015)
Studies have shown compelling evidence that suggests heading soccer ball might lead to brain trauma. Researchers have attempted to experimentally quantify head acceleration induced by soccer ball heading. A series of linear accelerometers as well as angular accelerometer were used to measure head accelerations. This method however is limited to measuring only head acceleration during the impact. However, it is essential to analyse the acceleration of the brain in addition to the acceleration of the head that takes place during a soccer-heading manoeuvre. Since the motion of the brain is almost impossible to be quantified experimentally, this work focuses on performing finite element (FE) analysis of soccer heading to study the motions of both the head and the brain during the impact. FE model of soccer ball was developed and validated against published experimental data as well as a more detailed model. Moreover, FE model of human head that consists of the skull, facial bones, cerebrospinal fluid (CSF) layer and the brain was also developed and validated against experimental data of blunt impact on human cadaver. Both validated models were assembled to perform the soccer heading simulations. Linear and angular accelerations of the skull and the brain generated are comparable to those of experimental data. However, it has underestimated the angular acceleration due to the absence of neck in the model, but with comparable acceleration profile. Linear and angular accelerations of the brain were found to be almost similar to those of the head, which is contradictory to our initial hypothesis. Further study such as ball impact on instrumented dummy skull is required to corroborate the findings. Nonetheless, the FE models were able to replicate the head accelerations sustained during soccer ball heading satisfactorily. The simulation results show that the models can be employed in finding protective materials that can reduce the accelerations, thus minimising the probability of suffering from long-term brain trauma due to soccer ball heading.